2017
DOI: 10.1371/journal.pone.0182654
|View full text |Cite|
|
Sign up to set email alerts
|

Management of the soybean cyst nematode Heterodera glycines with combinations of different rhizobacterial strains on soybean

Abstract: Soybean cyst nematode (SCN) is the most damaging soybean pest worldwide. To improve soybean resistance to SCN, we employed a soybean seed-coating strategy through combination of three rhizobacterial strains, including Bacillus simple, B. megaterium and Sinarhizobium fredii at various ratios. We found seed coating by such rhizobacterial strains at a ratio of 3:1:1 (thereafter called SN101) produced the highest germination rate and the mortality of J2 of nematodes. Then, the role of soybean seed coating by SN101… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Morphological, biochemical and molecular tools were used to identify Sneb159 as M. maritypicum . Coating seeds with B. simplex strain Sneb545 or compound bacteria SN101 promoted soybean resistance to H. glycines . For H. glycines , the females are important because they determine the size of a population and the extent of the damage .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Morphological, biochemical and molecular tools were used to identify Sneb159 as M. maritypicum . Coating seeds with B. simplex strain Sneb545 or compound bacteria SN101 promoted soybean resistance to H. glycines . For H. glycines , the females are important because they determine the size of a population and the extent of the damage .…”
Section: Discussionmentioning
confidence: 99%
“…Coating seeds with B. simplex strain Sneb545 or compound bacteria SN101 promoted soybean resistance to H. glycines. 37,46 For H. glycines, the females are important because they determine the size of a population and the extent of the damage. 47 Seeds treated with Sneb159 reduced population of juveniles and females in growth chamber and field experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exogenous stimulation of PGPR can induce a plant immune response, which can directly induce salicylic acid (SA)-and/or jasmonic acid (JA)-dependent defence responses 11,12 . Previous studies have indicated that the expression of SA-and JA-pathway-related genes could be up-regulated in host plants in response to SCN by coating seeds with bacteria [13][14][15] .…”
mentioning
confidence: 99%
“…Normally, nematicide and soil fumigation are proposed to control SCN [ 5 , 6 ]. However, such treatments seriously affect the ecological environment [ 7 , 8 ]. Therefore, simple tactics with fewer environmental risks have been sought to prevent SCN.…”
Section: Introductionmentioning
confidence: 99%